IMPLEMENTASI PROGRAM MENTORING DALAM MEMPERBAIKI KUALITAS BACAAN AL QUR’AN DI MADRASAH TSANAWIYAH AL ISLAM JAMSAREN SURAKARTA - Kurniawan, Aris; Hidayah , Nur; Sugiyat , Sugiyat (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
The problem of difficulty in reading the Qur'an and anything the hindrances for students must receive attention, not only for students at the elementary level but also for students at the junior and senior secondary levels. This research intends to determine the application of mentoring programs in improving the ability to read the Qoran, and to find out about supporting and inhibiting factors. This research used a qualitative-descriptive method and a phenomenological-naturalistic approach in MTs Al Islam Jamsaren Surakarta. Data collection was carried out by interview, observation, and documentation methods. Data analysis used Miles and Huberman's interactive data analysis techniques. Then, to test data validity, the researcher used triangulation techniques/methods. The result showed that the implementation of mentoring the Qur’an in MTs Al Islam Jamsaren Surakarta runs well. It is evidenced by the increasing of student’s quality of reading the Qur’an. Supporting factors of the success are enthusiasti, self-awareness, mandatory programand parent’s role. While the constraints are limited time and unconducive place.